Early Environments Shape Neuropeptide Function: The Case of Oxytocin and Vasopressin - Perry-Paldi, Adi; Hirschberger, Gilad; Feldman, Ruth; Zagoory-Sharon, Orna; Buchris Bazak, Shira; Ein-Dor, Tsachi (Frontiers in Psychology, 2019)
Oxytocin (OT) and vasopressin (AVP) are neuropeptides that govern the social-emotional functioning of humans. We contend that to fully understand their function, research should consider how they are flexibly fitted to maximize survival and reproduction given the variety of human experience. In a series of two studies, we show that early life stress is associated with change in the core function of OT and AVP in evolutionary predictable ways: Under high early life stress, AVP promotes threat-detection capabilities, whereas OT motivates non-selective proximity seeking to others. Conversely, under low early life stress these neuropeptides have an opposite, yet adaptive response: AVP promotes low vigilance and preservation of energy, whereas OT increases detection of interpersonal flaws. Our results demonstrate the plasticity of neuropeptide functioning that mirrors the variance in human social-emotional functioning.